Prodrugs for transdermal drug delivery – trends and challenges. (13th September 2016) - Ita, Kevin B.
Abstract: Prodrugs continue to attract significant interest in the transdermal drug delivery field. These moieties can confer favorable physicochemical properties on transdermal drug delivery candidates. Alkyl chain lengthening, pegylation are some of the strategies used for prodrug synthesis. It is usually important to optimize partition coefficient, water and oil solubilities of drugs. In this review, progress made in the field of prodrugs for percutaneous penetration is highlighted and the challenges discussed.